2017
DOI: 10.5194/cp-2017-95
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Ross Sea Dipole – Temperature, Snow Accumulation and Sea Ice Variability in the Ross Sea Region, Antarctica, over the Past 2,700 Years

Abstract: Abstract. High-resolution, well-dated climate archives provide an opportunity to investigate the dynamic interactions of climate patterns relevant for future projections. Here, we present data from a new, annually-dated ice core record from the eastern Ross Sea. Comparison of the Roosevelt Island Climate Evolution (RICE) ice core records with climate reanalysis data for the 1979–2012 calibration period shows that RICE records reliably capture temperature and snow precipitation variability of the region. RICE i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…In particular, blocking (ridging) events with a position and frequency determined by the intensity and position of the ASL (Renwick, 2005) have been identified as a major driver of snow precipitation in the eastern Ross Sea region, enhancing meridional flow across the eastern Ross Sea . The principal tropical teleconnection associated with the Rossby wave propagation from the western tropical Pacific exerts its influence on the entire Ross Sea region, with opposing influence between the east and west Bertler et al, 2017), which explains some of the differences observed in these two regions.…”
Section: Victoria Land (Vl)mentioning
confidence: 99%
“…In particular, blocking (ridging) events with a position and frequency determined by the intensity and position of the ASL (Renwick, 2005) have been identified as a major driver of snow precipitation in the eastern Ross Sea region, enhancing meridional flow across the eastern Ross Sea . The principal tropical teleconnection associated with the Rossby wave propagation from the western tropical Pacific exerts its influence on the entire Ross Sea region, with opposing influence between the east and west Bertler et al, 2017), which explains some of the differences observed in these two regions.…”
Section: Victoria Land (Vl)mentioning
confidence: 99%
“…during two austral summer field seasons, 2011–2012 and 2012–2013. Roosevelt Island is a high snow accumulation site (Bertler and others, 2018) with the potential for a highly resolved record. The RICE BIZ occurs from 500 m depth to bedrock, which was reached at 764 m. This part of the core contained a higher number of fractures, representing a potentially significant loss of ice for CFA.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the integrity of planned measurements, particularly gases, ice cores need to be kept frozen at −18°C or colder (Ikeda-Fukazawa and others, 2005). Due to the relatively warm summertime temperatures at Roosevelt Island (Bertler and others, 2018), core curation in the field was an important challenge. Once the cores were drilled, they were kept in core rest buffer shelving (SF) to relax for up to 2 weeks.…”
Section: Rice Site Drilling and Core Storagementioning
confidence: 99%
“…The RICE δ 18 O record, situated on Roosevelt Island on the Ross Ice Shelf, is more influenced by air masses from the eastern Ross Sea sector than the rest of the West Antarctic Ice Sheet region, which is influenced predominantly by air masses from the Amundsen Sea (Neff et al, 2015;. Moreover, borehole temperature and δ 15 N thermal fractionation records at RICE highlight some notable differences in the isotope temperature reconstruction, which suggest that sea ice extent exerts an important control, perhaps masking aspects of the longer-term temperature trends in the region (Bertler et al, 2017). Over the period from 0 to 1900 CE the ECHAM temperature scaling suggests that the mean cooling trends are −0.38 • C 1000 yr −1 for the East Antarctic Plateau, −0.47 • C 1000 yr −1 for the West Antarctic Ice Sheet, −0.52 • C 1000 yr −1 for the Antarctic Peninsula and −0.34 • C 1000 yr −1 for Victoria Land.…”
Section: Long-term Trends In Weighted Reconstructionsmentioning
confidence: 97%